(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, the local existence and uniqueness of a chemotaxismodel with a moving boundary are considered by the contraction mapping principle, and the explicit expression for the moving boundary is formulated. In addition, the finite-time blowup and chemotactic collapse of the solution for such kind of problem are discussed.